RC-frames infilled with rc infill-walls for seismic retrofitting - Georgiou, Elpida (Department of Civil Engineering and Geomatics, Faculty of Engineering and Technology, Cyprus University of Technology, 2020)
The seismic retrofitting of existing multi-storey multi-bay reinforced concrete (RC) frame buildings by the conversion of selected bays into new RC infilled walls is the subject of this research work. The parametric study of the contribution of dowels that connect a new RC infill wall to the surrounding RC frame members was performed through nonlinear dynamic analyses of a numerical finite element (FE) model. The FE model was simulated in DIANA finite element analysis (FEA) software in order to study the effectiveness of the seismic retrofitting of existing structures with the conversion of selected bays into new infilled RC walls for the retrofitting of a multi-storey multi-bay RC frame building. A two-dimensional (2D) frame was modeled, and nonlinear transient analyses were performed to calibrate it using the experimental results obtained from a full-scale experiment found in the literature. The description of the experimental results and of the FE model simulation of the test specimen is provided along with a comparison between the experimental results and the numerical ones. Based on the preliminary results it was concluded that the number of dowels used in the experiment resulted in a monolithic behavior of the RC infilled frame. In order to complement the experimental results and to study the interaction between RC infills and the bounding frame both at the global and local level, numerical simulation experiments were performed by reducing the number of dowels starting from a spacing of 100mm (monolithic) to no dowels. For each scenario, nonlinear response-history analysis was performed and an evaluation of the numerical results of each of these scenarios was subsequently performed. The parametric study of the number of dowels connecting the wall to the bounding frame is presented and conclusions are drawn. The parametric results provide a basis for the development of a general model for the design of RC infills in existing RC frames, particularly regarding the connection details of the new RC infill walls to the existing bounding frame.
Keywords: Retrofitting seismic deficient structures; RC infill walls; Modeling of dowels; Finite element model; Nonlinear numerical parametric study